Role of the Cytosolic Heat Shock Protein 70 Ssa5 in the Ciliate Protozoan Tetrahymena thermophila. (13th February 2015) - Fukuda, Yasuhiro; Akematsu, Takahiko; Attiq, Rizwan; Tada, Chika; Nakai, Yutaka; Pearlman, Ronald E.
Abstract Heat shock protein 70 (Hsp70) is a member of a family of conserved chaperone proteins whose function is well investigated in many model organisms. Here we focus on an Hsp70 called Ssa5 in the ciliate protozoan Tetrahymena thermophila, and reveal that its translation is heat inducible as for general Hsps. Moreover, the protein is abundantly expressed in the cytoplasm during sexual reproduction (conjugation) as well as in response to heat‐stress. Knocking out of SSA5 (ΔSSA5) does not affect the survival of the cell under heat‐stress, likely due to other Hsp70 paralogs compensating for the defect. During conjugation, ΔSSA5 leads to a fertilization defect in which the two pronuclei are in close proximity but never fuse. The unfertilized pronuclei differentiate, resulting in a heterokaryon with developed haploid germline and somatic nuclei. In addition, degeneration of the parental somatic nucleus is not affected. These results suggest a specific involvement of Ssa5 in pronuclear fusion and fertilization.